Nanomedicine in fungal keratitis: current applications and future prospects - Xiao, Yuyang; Yang, Yifei; Sun, Binyu; Yang, Meng; Lang, Jiamiao; Dong, Mintao; Chen, Zengsihan; Chen, Shanshan; Wang, Shengfeng (Frontiers in Microbiology, 2025)
Fungal keratitis (FK) poses a significant public health challenge, causing substantial harm to human health and the socio-economic landscape. However, due to the special anatomical and physiological characteristics of the eye, the current therapeutic drugs for FK are not effective, which brings obstacles to the clinical treatment of FK. Nanomedicine is a new therapeutic method that has emerged in the field of FK therapy in recent years. On the one hand, nanomaterials can directly kill fungi by separating ions, and on the other hand, the drug delivery system (DDS) composed of nanomaterials can target and deliver traditional drugs to the affected area and play a bactericidal role, with a significantly higher effect than traditional therapy. This review begins with a bibliometric analysis of research progress in FK nanomedicine. Then we describe the mechanism and effect of various nanomedicine in the treatment of FK from the perspective of direct and indirect treatment, focusing on the attack of nanomedicine on biofilm and DDS composed of nanomaterials. Finally, this field is prospected in order to provide new insights and ideas for the development of FK nanomedicine.